ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HASIL AUDIT DILINGKUNGAN PEMERINTAHAN DAERAH (STUDI KASUS DI INSPEKTORAT KOTA KUPANG) - YUNINGSIH NITA CHRISTIANI (Unitri Press, 2022)
The purpose of this study was conducted to obtain: factor-faktor affecting the quality of the audit .This study was conducted in inspekorat kupang .An independent variable in this study the independence of (X1 ), objektifitas (X2 ), integrity , (X3 ) job experience , (X4) competence (X5), and motivation (X6 ).The quality of the audit dependent variable (Y ).The data used is primary data . Respondents in this research is an auditor that is work in kota kupang inspectorate.Technique with the methods of sampling the sample purposive with 33 respondents.Data collection method that is by using questionnaires for respondents.Scale of measurement of the ordinal of data.Data analyzed by regression analysis with SPSS program assistance.Based on the research is objektifitas indepedensi and not influenced the quality of the audit and integrity, work experiences, competence, and motivation have had a positive impact on the quality of the audit in an auditor kota kupang.Keyword: independence of, objektifitas, integrity, job experience, competence, motivation.